The application of sliding mode observers to fault detection and isolation for multilevel converters - Shao, Shuai (2015)
Multilevel converters have received significant interest recently as a result of their high power capability and good power quality. However due to the large number of sensitive components including power semiconductor devices and capacitors used in such circuits there is a high likelihood of component failures.